Effect of Methionine Diet on Time-Related Metabolic and Histopathological Changes of Rat Hippocampus in the Model of Global Brain Ischemia - Kovalska, Maria (Biomolecules, 2020)
Hyperhomocysteinemia (hHcy) represents a strong risk factor for atherosclerosis-associated diseases, like stroke, dementia or Alzheimer’s disease. A methionine (Met)-rich diet leads to an elevated level of homocysteine in plasma and might cause pathological alterations across the brain. The hippocampus is being constantly studied for its selective vulnerability linked with neurodegeneration. This study explores metabolic and histo-morphological changes in the rat hippocampus after global ischemia in the hHcy conditions using a combination of proton magnetic resonance spectroscopy and magnetic resonance-volumetry as well as immunohistochemical analysis. After 4 weeks of a Met-enriched diet at a dose of 2 g/kg of animal weight/day, adult male Wistar rats underwent 4-vessel occlusion lasting for 15 min, followed by a reperfusion period varying from 3 to 7 days. Histo-morphological analyses showed that the subsequent ischemia-reperfusion insult (IRI) aggravates the extent of the sole hHcy-induced degeneration of the hippocampal neurons. Decreased volume in the grey matter, extensive changes in the metabolic ratio, deeper alterations in the number and morphology of neurons, astrocytes and their processes were demonstrated in the hippocampus 7 days post-ischemia in the hHcy animals. Our results suggest that the combination of the two risk factors (hHcy and IRI) endorses and exacerbates the rat hippocampal neurodegenerative processes.